A novel glyceroglycolipid from brown algae Ishige okamurae improve photoaging and counteract inflammation in UVB-induced HaCaT cells. (5th January 2022) - Xiao, Zhenbang; Yang, Shengtao; Liu, Yi; Zhou, Chunxia; Hong, Pengzhi; Sun, Shengli; Qian, Zhong-Ji
Abstract: Background: Excessive exposure to Ultraviolet (UV) rays can cause premature skin aging. Ishigoside (IGS) is a new glyceroglycolipid compound isolated from brown algal Ishige okamurae, However, whether it can protect the skin from (Ultraviolet-B) UVB damage has not been illuminated. Methods: The in vitro anti -photoaging effect of IGS was conducted in UVB-induced HaCaT. The HaCaT cells were divided into the following five groups: (1) cells didn't suffer from UVB irradiation or IGS treatment. (2–5) Cells were treated with various concentrations of IGS (0, 10, 50, and 100  μ M) and irradiated by 40 mJ/cm 2 UVB. The Matrix metalloproteinase (MMP) of photoaging process was determined by ELISA kits and the latent interaction between IGS and MMP was further performed by molecular docking. The crucial signaling pathway proteins involved in the collagen synthesis and degradation were subsequently evaluated by Western blotting, immunofluorescence and EMSA. Results: IGS effectively suppresses the high expressions and secretions of matrix metalloproteinases (MMPs) and photo-inflammation by blocking MAPKs, AP-1 and NF-κB. Meanwhile, increasing antioxidant enzyme expression. Molecular docking results suggest that inhibition of IGS on MMPs may be attributed to its hydrogen supply and hydrophobic capacity. In addition, IGS enhanced procollagen production by upregulating the TGF-β/Smad pathways. Conclusions: IGS exhibited anti -photoaging activity in UVB-damage HaCaT. These effects might be a contribution by its suppression of MMPs expression via MAPKs, AP-1 and NF-κB pathway and have anti-oxidative and anti-inflammatory effects. Therefore, IGS has the great potential to become skin-care products or functional foods for preventing skin photoaging. Graphical abstract: Image 1 Highlights: Ishigoside is the functional ingredient of edible brown algae Ishige Okamurae. Photoprotectant ishigoside has the potential to develop into healthy food. Ishigoside reduced matrix metalloproteinases expression and alleviate inflammation via affecting the MAPK/AP-1 and NF-κB pathways. Ishigoside can inhibitory binding with MMPs by molecular docking analysis.